1987
DOI: 10.1111/j.1476-5381.1987.tb16842.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tachykinins on inositol phospholipid hydrolysis in slices of hamster urinary bladder

Abstract: 1Tachykinin-stimulated inositol phospholipid hydrolysis was examined in slices of hamster urinary bladder.2 In the presence of lithium, to inhibit inositol monophosphatase activity, substance P, eledoisin and related tachykinins induced large, dose-dependent increases in [3H]-inositol monophosphate accumulation. 3 The responses to substance P and eledoisin were not antagonized by the cholinoceptor antagonist, atropine. 4 The rank order of potency for various tachykinins was kassinin> neurokinin A> neurokinin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

1987
1987
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 16 publications
3
17
1
Order By: Relevance
“…The methodology was adapted from Berridge et al (1982) and Bristow et al (1987 Berridge et al (1982). Distilled water (0.30 ml) and chloroform (0.31 ml) were added, the samples centrifuged (1000 g for 5 min).…”
Section: Phosphatidylinositol Hydrolysis Measurementmentioning
confidence: 99%
“…The methodology was adapted from Berridge et al (1982) and Bristow et al (1987 Berridge et al (1982). Distilled water (0.30 ml) and chloroform (0.31 ml) were added, the samples centrifuged (1000 g for 5 min).…”
Section: Phosphatidylinositol Hydrolysis Measurementmentioning
confidence: 99%
“…All three tachykinin receptor types stimulate phosphoinositide metabolism. NK1-stimulation of this pathway has been reported in guinea-pig ileum longitudinal smooth muscle (Watson & Downes, 1983); NK2-stimulation in the hamster urinary bladder (Bristow et al, 1987) and NK3 stimulation in myenteric plexus of guineapig ileum (Guard et al, 1988). Recently, Nakajima et al (1992) demonstrated that individual tachykinin receptors stably transfected in Chinese hamster ovary cells couple to phosphoinositide hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…UCI1 and LRM55 cells have been shown to express NK, receptors (Johnson & Johnson, 1992;Perrone et al, 1986). In order to determine whether other tachykinin receptors are also present on LRM55 and UCIl cells we measured the ability of senktide, a selective NK3 agonist (Wormser et al, 1986), and [PAla8]NKA(4-10), a selective NK2 agonist (Rovero et al, 1989), to stimulate [3H]-inositol phosphate accumulation, as both of these receptor types have been shown to stimulate inositol phospholipid hydrolysis (Bristow et al, 1987;Guard et al, 1988).…”
Section: Characterization Of Tachykinin Receptor Types On Cell Linesmentioning
confidence: 99%
“…However, there is evidence that, depending on the tissue, all the receptor subtypes are capable of mediating PIP2 hydrolysis. Thus PIP2 hydrolysis has been observed in NK2-type tissues such as the rat ileum and hamster urinary bladder [14,15]. Substance P and related tachykinins also stimulate inositol phospholipid hydrolysis in guinea pig ileum longitudinal muscle-myenteric plexus preparations, an example of NK3-type tissue [16].…”
Section: Discussionmentioning
confidence: 99%